Molecular engineering two-dimensional hybrid perovskites for light emission - Hu, Hongwei (2018)
Organic-inorganic hybrid perovskites have emerged in recent years as one of the most promising materials for solution-processed electronics and optoelectronics including solar cells, light-emitting diodes (LED) and field-effect transistors (FET). Combining the rigid inorganic framework with soft organic materials, these hybrid perovskites provide the opportunity for investigating organic-inorganic interactions at the molecular scale. Using a molecular approach, this Ph.D. work explored a series of novel organic-inorganic hybrid perovskites targeting luminescence-related applications including LEDs and color-conversion phosphors. The structure-property relation was investigated and the underlying photophysical mechanism for the versatile luminescence was studied. The applications of these perovskites as light emitters in multicolored LED, white LED and long-lifetime phosphors were demonstrated...